Effective Management Practices: A Comprehensive Approach to Organizational Success - Feriandy; Nurwulan Kusuma Devi; Ifah Masrifah (PT FORMOSA CENDEKIA GLOBAL, 2024)
Effective management practices are critical in driving organizational performance and ensuring long-term success. This study explores the relationship between management techniques and organizational outcomes. By examining existing literature, this research identifies key management practices that contribute to improving efficiency, employee satisfaction, and financial performance. Through a qualitative approach, this paper presents case studies from various industries to understand how these practices are applied and their impact. The findings highlight the importance of leadership, communication, and strategic planning in fostering organizational growth and sustainability